Communication strategies used by Chinese students from China in spoken English / Liu Qing Hua - Liu, Qing Hua (2010)

(untitled)
This study evaluates the use of Communication Strategies which are employed by Second Language Acquisition (SLA) learners. A comprehensive review of the relevant literature from the last decade is done with focus on the particular consideration given to the different ways in which Communication Strategies have been defined under the corresponding influences in regard to the organization of strategy taxonomies. This study also seeks to examine how learners of second language perform in communicative tasks especially where they are confronted with linguistic problems and communication barriers. It also aims at identifying the communication strategies used by the students from China studying in Malaysia to bridge the discrepancy between their communicative capabilities and their limited communicative resources. An attempt is also made to discover the problems encountered by them in communication which calls for the use of the communication strategies. The methodology used in this study is a Qualitative Research method where the responses of the students in their communications based on three different tasks given is collected. The responses/utterances collected are then analysed to identify both the problems that are encountered as well as the communication strategies that are used. As such, this research on second language learners' communicative strategies provides an elaborate framework for analyzing how learners manage to express themselves in spite of their limited knowledge of the target language. xv In addition, this study will also attempt to examine the practical application of communication strategies. Many studies (Tarone, 1977; Corder, 1983) dealing with the identification and classification of the linguistic manifestations have identified the gap that exist between communicative intentions and the linguistic resources available to the learner to realize them. Other studies have been undertaken to investigate the psychological processes underlying the use of Communication Strategies in the event that the students have problems in conversations (Faerch & Kasper, 1980). A more elaborate cognitive approach has been reached in the works of Poulisse (1990) and Bialystok (1990). In this study, the analysis of communication strategies will be based on Dornyei‟s (1995) classification, namely avoidance strategy and compensatory strategy. Besides analysing the strategies used by the subjects under the respective categories, this study will also tabulate and calculate the frequency of communication strategies identified. The purpose is to identify which of the communication strategies are preferred more by the subjects. All these are discussed in the dissertation.